SINTESIS SENYAWA ETILENDIAMIN KALANON MELALUI REAKSI ADISI GUGUS ETILENDIAMIN TERHADAP IKATAN RANGKAP C7-8 DAN UJI AKTIVITAS ANTILEUKEMIA TERHADAP SEL LEUKEMIA L1210 - Mochamad Chasani; Eva Vaulina; Ponco Iswanto; M. Hanafi M. Hanafi (Universitas Jenderal Soedirman, 2008)
Calanone is a natural compound which could be isolated from tree bark of Calophyllum biflorum Hend and WS ( 0,37 % w/w, crude extract) which have been potency as antileucemia drug (IC50= 59,4 ug/mL). Based on the research, the compound can be used as an anti leukemia drug if it value of IC50 < 10 ug/mL. So the aim of this research are in order to get higher calanone activity by modified of double bond carbon-carbon and to obtained several compounds as well which has a higher activity than calanone of its original compound. Several compounds, several compound can be obtained by modified of doble bond carbon-carbon by ethylendiamine group and antileukemia test of the new compound calanone derivatives towards L1210 leukemia cell. The result of the analysis, using thin layer chromatography with eluent methanol:dichlorometane ( 1:6) , give Rf at 0.51 and initial melting point at range 149oC – 151oC. Infra red spectrophotometry and mass spectrometry were used to identify the synthesized product. The result showed that the mass spectra of ethylendiamine calanone give molecular ion at 449 (M+- H2O, NH3) and ions fragmen at m/e 449; m/e 434; m/e 393; m/e 105, m/e 77. Infra red spectra of its compound showed new peaks at 1620 cm -1 and 1063 cm -1. The activity value toward leukemia cell was IC50= 46,28 µg/mL and its value higther than calanone origin.